Implementation of Financing Policy for UMKM by Bank Syariah Indonesia (BSI) Based on National Economic Recovery Objectives - Rolib Sitorus; Jessy, Jessy (Indonesian Journal of Banking and Financial Technology, 2023)
This research aims to determine the implementation of financing policies for MSMEs by Bank Syariah Indonesia (BSI) based on national economic recovery objectives and determine whether or not the national economic recovery objectives have been achieved. This research uses normative-empirical research methods. This research examines primary data, namely the results of interviews with parties related to the distribution of MSME financing, then examines secondary data consisting of primary legal material, secondary legal material and tertiary legal material. Research data collection methods are carried out through books, journals and articles and interviews related to the problems being researched. The type of research approach used is a qualitative research approach with descriptive presentation. The data collected is analyzed using descriptive analysis techniques. The results of this research are the implementation of financing policies for UMKM by Bank Syariah Indonesia (BSI) KC Kuala Simpang during the COVID-19 pandemic in the form of margin subsidies as regulated in Minister of Finance Regulation Number 138/PMK.05/2020 concerning Procedures for Providing Interest/Subsidies Margin in order to support the implementation of the National Economic Recovery Program and restructuring policy stimulus as regulated in Financial Services Authority Regulation Number 11/POJK. 03/2020 concerning National Economic Stimulus as a Countercyclical Policy for the Impact of the Spread of Corona Virus Disease 2019 has been implemented in accordance with Law Number 21 of 2008 concerning Sharia Banking and the Fatwa issued by DSN-MUI.